2021
DOI: 10.3390/jcm10122719
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bundle Branch Block on Permanent Pacemaker Implantation after Transcatheter Aortic Valve Implantation: A Meta-Analysis

Abstract: Data regarding the impact of infra-Hisian conduction disturbances leading to permanent pacemaker implantation (PPI) after transcatheter aortic valve implantation (TAVI) remain limited. The aim of this study was to determine the impact of right and/or left bundle branch block (RBBB/LBBB) on post-TAVI PPI. We performed a systematic literature review to identify studies reporting on RBBB and/or LBBB status and post-TAVI PPI. Study design, patient characteristics, and the presence of branch block were analyzed. Od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…5,8,12,13 Given the close anatomic relationship between the aortic valve and the His bundle, as well as left bundle branch, studies on post-TAVR conduction system abnormalities have largely focused on high-grade/complete atrioventricular block and LBBB. 5,8,[14][15][16] In contrast, the mechanistic and clinical aspects of post-TAVR RBBB are far less understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,12,13 Given the close anatomic relationship between the aortic valve and the His bundle, as well as left bundle branch, studies on post-TAVR conduction system abnormalities have largely focused on high-grade/complete atrioventricular block and LBBB. 5,8,[14][15][16] In contrast, the mechanistic and clinical aspects of post-TAVR RBBB are far less understood.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, ≈10% to 20% of patients with post-TAVR LBBB were found to progress toward high-grade/complete atrioventricular block. 8,15,16 This suggests that post-TAVR RBBB may be a more potent indicator of severe infrahisian injury versus post-TAVR LBBB, although more studies are required to verify this hypothesis. Interestingly, all 3 patients who had left anterior fascicular block at baseline and new-onset RBBB post-TAVR manifested with high-grade atrioventricular block, indicating that multiple hits to the conduction system may result in eventual infrahisian failure.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline right bundle branch block (RBBB) is a major electrical disturbance, independent of age or left ventricular ejection fraction, 9 increasing the risk for atrioventricular block (AVB) leading to PPI 4–8,10–16 . In contrast, preexisting LBBB was previously known not to increase the risk of post‐TAVR conduction abnormalities 8,9,15,17,18 . However, a recent meta‐analysis found that baseline LBBB is associated with an increased incidence of PPI (odds ratio [OR]: 1.45; 95% confidence interval [CI]: 1.12−1.77) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Baseline right bundle branch block (RBBB) is a major electrical disturbance, independent of age or left ventricular ejection fraction, 9 increasing the risk for atrioventricular block (AVB) leading to PPI. [4][5][6][7][8][10][11][12][13][14][15][16] In contrast, preexisting LBBB was previously known not to increase the risk of post-TAVR conduction abnormalities.…”
Section: Preexisting Conduction Abnormalitiesmentioning
confidence: 99%
“…Nevertheless, the indication for PPI is still an area of uncertainty [ 1 , 2 , 3 , 4 , 5 , 6 ]. The phenomenon of new onset left bundle branch block (LBBB) gained attention in several scientific reports [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], as it has been reported to be associated with increased all-cause and cardiovascular mortality and an increased necessity of subsequent PPI [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%